Principles of Therapeutic Discourse of Patients with Generalized Anxiety Disorder with Cognitive-Behavioral Therapy Approach - Rahimian, Jalal; Mohamadpour, Fereshteh (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:Opening conversations in psychotherapy discourse is very sensitive. Therefore, identifying the principles of how opening conversations in such discourses is extremely important. The present study uses the conversation analysis approach to find the principles of opening conversation in the therapeutic discourse of treatment sessions for patients with generalized anxiety disorder (GAD) based on the Cognitive-Behavioral Therapy (CBT) approach. Materials and Methods:The method used in this research is based on the logic of qualitative research. The corpus used in this study included 2520 minutes of conversation in psychotherapy sessions. Participants in this study were selected from both sexes. To analyze the data, methods of conversation analysis, word counting and finding keywords in the text have been used. Also, ATLAS ti. Computer software has been used to construct and present the verbal pattern. Results:The results of data analysis show that opening conversation pattern in psychotherapy sessions consists of five stages of which only the “Identification-recognition sequence” is used in the initial treatment sessions and the rest is used in all sessions. Psychologists have opened conversations in all psychotherapy sessions.It takes about 5 to 10 minutes to open a conversation. Conclusion:The abundance of data also shows that when using the general pattern of conversation initiation sequence, there was no verbal difference between psychotherapists and male and female clients, and all behaved according to the rules governing psychotherapy sessions. This confirms the high sensitivity of the type of approach to clients and how to begin to communicate in conversations related to therapeutic discourse.